Correlation between Candida spp. and DMFT index in a rural population - Sheila Cavalca Cortelli; Juliana Campos Junqueira; Ivan da Silva Faria; Cristiane Yumi Koga Ito; José Roberto Cortelli (Universidade Estadual de Campinas, 2015)
Oral presence of Candida spp. was correlated with caries experience (dmft/DMFT index) in a rural population. dmft/DMFT index were evaluated in individuals between 6-12 years of age (n=57), 13-18 years of age (n=48) and 19-45 years of age (n=54). For the isolation of Candida spp., saliva samples were collected and spread on Sabouraud dextrose agar plates. The number of colony- forming units per plate (CFU/plate) was calculated and the isolates were identified. Data were analyzed by Chi-square and Spearman's correlation coefficient (p<0.05). The mean value obtained for dmft/DMFT index were 6.63 (6-12 years of age), 11.44 (13-18 years of age), and 21.16 (19-45 years of age). Candida spp. were isolated from 60% of the individuals between 6-12 years of age, 70% of the individuals between 13-18 years of age and 95% of the individuals between 19-45 years of age. In the 13-18 years of age group a positive correlation between Candida and DMFT was observed. No correlation was observed among Candida and DMFT index in the others age groups. In conclusion, the presence of Candida spp. in the oral cavity seem to be related with past caries experience in young adults from 13 to 18 years of age.